2022
DOI: 10.1515/psr-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Fused pyrrolo-pyridines and pyrrolo-(iso)quinoline as anticancer agents

Abstract: This work emphasizes the synthesis strategies and antiproliferative related properties of fused pyrrolo-pyridine (including indolizine and azaindoles) and pyrrolo-(iso)quinoline derivatives recently reported in literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…Given the information discussed above, the focus of our current study is to synthesize new derivatives, building upon our previous research on N-heterocycle systems, [12][13][14] while remaining aligned with our keen interest in exploring chemical compounds with physiological activity. [15][16][17][18][19] This article presents our findings, including the synthesis, characterization, and antitumor evalution of several new N-heterocycle monoquaternary salts.…”
Section: Introductionmentioning
confidence: 99%
“…Given the information discussed above, the focus of our current study is to synthesize new derivatives, building upon our previous research on N-heterocycle systems, [12][13][14] while remaining aligned with our keen interest in exploring chemical compounds with physiological activity. [15][16][17][18][19] This article presents our findings, including the synthesis, characterization, and antitumor evalution of several new N-heterocycle monoquaternary salts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several other pyrrolo[1,2- a ]pyrazine alkaloids, such as dibromofakelin and longamide B, exhibit multiple biological activities, including cytotoxicity [ 5 ]. Moreover, our group has reported pyrrole-fused heterocyclic derivatives with an indolizine, pyrrolopyridazine, pyrrolo(iso)quinoline, and pyrrolophenathroline core, with part of them showing considerable anticancer properties [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 3 ]. As a result of this approach, important advances have been achieved in antimicrobial therapy, some of the present drugs from the market have a hybrid structure ( Figure 1 ) and some hybrid structures are in different clinical trials ( Figure 2 ) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that azines are privileged scaffolds in current medicinal chemistry and drug discovery, possessing a large variety of biological activities, such as: antibacterial, antifungal, antiplasmodial and antimalarial, anthelmintic, antitubercular, antiviral, anticancer, anti-inflammatory, antihypertensive, diuretic, antithrombic, anticoagulant, antidepressant, anxiolytic, anticonvulsant, analgesic, antiulcer, antidiabetic, antihistaminic, etc. [ 4 , 5 , 6 , 7 , 8 ]. As a matter of fact, the greatest majority of the existing drugs from the market contain in their structure a nitrogen heterocycle, some of them being a hybrid structure ( Figure 1 ), which justifies the demand of the pharmaceutical industry for such drugs with nitrogen heterocycle skeleton.…”
Section: Introductionmentioning
confidence: 99%